Profit with Purpose, Making Banking on Women Impactful : Learnings from BLC Bank Lebanon, Garanti Bank Romania, Garanti Bank Turkey - International Finance Corporation (International Finance Corporation, Washington, DC, 2016)
The overall objective of this report is to learn about the results of the International Finance Corporation (IFC) ‘Banking on Women Program’ (BoW) in Europe, Central Asia, the Middle East and North Africa (EMENA) as well as other Banking on Women programs. Established in 2010, IFC’s ‘Banking on Women Program’ uses IFC’s investment capital to help financial institutions around the world with lending track records to small and medium enterprises (SMEs) to profitably expand their portfolios and provide women entrepreneurs with access to finance. IFC also works with financial institutions to deepen their ability to reach women-owned businesses through segmenting their target market, positioning their brand and repositioning their products to reach female borrowers. Garanti Bank Romania, BLC Bank in Lebanon, both IFC client banks, and Garanti Bank Turkey3, were selected for this publication as individual case studies. Each of the three case studies looks at the existing capacity and performance of each of these banks in terms of serving women entrepreneurs. In doing so, the study places particular emphasis on the extent to which these banks are able to deliver their women banking programs in a commercially viable, self-sufficient manner that is based on the bank’s own in-house resources and capacities. Where possible, each study also aims to understand if and how the female borrower segment has affected each bank’s business (bottom line, sustainability and growth targets). A separate and parallel assessment of this program looks at the impact of the program on the end beneficiaries, i.e. women-owned SMEs. This beneficiary survey will provide insights into how effectively the bank’s female borrowers are reached and served. Ultimately, this study aims to generate learning for IFC and its client banks in order to strengthen the design and delivery of the banks’ BoW program, as well as IFC engagements in this area.